Increase of α-dicarbonyls in liver and receptor for advanced glycation end products on immune cells are linked to nonalcoholic fatty liver disease and liver cancer. (1st January 2021) - Petriv, Nataliia; Neubert, Lavinia; Vatashchuk, Myroslava; Timrott, Kai; Suo, Huizhen; Hochnadel, Inga; Huber, René; Petzold, Christina; Hrushchenko, Anastasiia; Yatsenko, Andriy S.; Shcherbata, Halyna R.; Wedemeyer, Heiner; et al.
ABSTRACT: Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver with a very poor prognosis and constantly growing incidence. Among other primary risks of HCC, metabolic disorders and obesity have been extensively investigated over recent decades. The latter can promote nonalcoholic fatty liver disease (NAFLD) leading to the inflammatory form of nonalcoholic steatohepatitis (NASH), that, in turn, promotes HCC. Molecular determinants of this pathogenic progression, however, remain largely undefined. In this study, we have focussed on the investigation of α-dicarbonyl compounds (α-dC), highly reactive and tightly associated with overweight-induced metabolic disorders, and studied their potential role in NAFLD and progression toward HCC using murine models. NAFLD was induced using high-fat diet (HFD). Autochthonous HCC was induced using transposon-based stable intrahepatic overexpression of oncogenic NRAS G12V in mice lacking p19 Arf tumor suppressor. Our study demonstrates that the HFD regimen and HCC resulted in strong upregulation of α-dC in the liver, heart, and muscles. In addition, an increase in α-dC was confirmed in sera of NAFLD and NASH patients. Furthermore, higher expression of the receptor for advanced glycation products (RAGE) was detected exclusively on immune cells and not on stroma cells in livers of mice with liver cancer progression. Our work confirms astable interplay of liver inflammation, carbonyl stress mediated by α-dC, and upregulated RAGE expression on CD8 + Tand natural killer (NK) cells in situ in NAFLD and HCC, as key factors/determinants in liver disease progression. The obtained findings underline the role of α-dC and RAGE + CD8 + Tand RAGE + NK cells as biomarkers and candidates for a local therapeutic intervention in NAFLD and malignant liver disease. Graphical abstract: uf0001